2023
DOI: 10.3390/ijfs11010020
|View full text |Cite
|
Sign up to set email alerts
|

Pricing Ability of Carhart Four-Factor and Fama–French Three-Factor Models: Empirical Evidence from Morocco

Abstract: In this study, the reliability of the Fama–French Three-Factor model (FF3F) and the Carhart Four-Factor model (C4F) is examined thoroughly. In order to determine which of the asset pricing models is the best to explain portfolio returns on the Moroccan share market, these two models are indeed evaluated in the Moroccan market. Additionally, it is worth mentioning that five years of monthly data from the firms that listed on the Casablanca Stock Exchange are used in this research, as well over the period of nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Specifically, according to Hearn (57), the impact of size was far greater in Egypt and Tunisia than it was in Morocco. In addition, this finding is further supported by Benali et al (58), who concluded that the excess return of equities in Moroccan markets is not explained by market, size, or value factors. Furthermore, in five growing economies in the Pacific Basin, Chui, and Wei (59) looked at the connections between stock returns, the beta of the market, book-to-market equity (B/M), and size.…”
Section: Literature Reviewsupporting
confidence: 74%
See 1 more Smart Citation
“…Specifically, according to Hearn (57), the impact of size was far greater in Egypt and Tunisia than it was in Morocco. In addition, this finding is further supported by Benali et al (58), who concluded that the excess return of equities in Moroccan markets is not explained by market, size, or value factors. Furthermore, in five growing economies in the Pacific Basin, Chui, and Wei (59) looked at the connections between stock returns, the beta of the market, book-to-market equity (B/M), and size.…”
Section: Literature Reviewsupporting
confidence: 74%
“…He noted that the spillover effect of an event from a country affects the effectiveness of the Fama-French model in another country. In addition, the reliability of the Fama-French threefactor model also fluctuates according to the economic status of a country (55) since several studies-Hearn and Piesse (56), Hearn (57), and Benali et al (58)-examined the usefulness of the three-factor model in explaining the cross-section of stock return in some stock markets in Africa and revealed a few different findings. Specifically, according to Hearn (57), the impact of size was far greater in Egypt and Tunisia than it was in Morocco.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their finding implied that CAPM is the least effective model as it does not explain the variations in stock returns. Meanwhile when comparing FF3F model and FF5F; both models provide incomplete descriptions of the returns, nevertheless, FF5F was found to be superior to FF3F (Taib & Benfeddoul, 2023) (Ragab, Abdou, & Sakr, 2020) (Salameh, 2020) (Alrabadi & Alrabadi, 2018) .These results could be mainly attributed to the fact that emerging markets have different features than developed markets. Thin trading, illiquidity, a small number of listed firms, a small number of investment research organizations, and less corporate governance enforcement are characteristics of emerging markets which lead to market inefficiency.…”
Section: Introductionmentioning
confidence: 91%
“…The beta measures the systematic risk of stock and is calculated by comparing the stock returns to the market returns (Lee, Hooy, & Brooks, 2023). This model has been applied extensively and has been verified through empirical testing all over the world, continuing to generate successful results due to its simplicity (Alaoui Taib & Benfeddoul, 2023;Kostin, Runge, & Adams, 2021). Conversely, 1FM validity has been questioned as poor performing model because of data abnormality.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%